The development of height and weight measuring instruments for web-based Anthropometric tests - Putri Yuliana Mahardika; Yohandri Yohandri (invotek, 2021)
Early childhood talent identification sport programs are needed to decide the potential of children in certain sports. It is expecting that children will be able to maximize sports achievements according to their talents. To find out a human's talent in sports, several parameters can be used for a measurement. One of them is the anthropocentric test, which is a series of processes for measuring the dimensions of the human body with in the form of body height and weight. Based on the results of measurement analysis, children will be able to identify their sport talents. Therefore, a website-based height and weight measurement system was developed that is able to provide information on measurement results and talents identification. The development of this tool uses the ESP 32 Dev Kit Module as a micro controller, an ultrasonic sensor for height sensors and a load cell for a weight sensor. The data are sent to the database contained on the website for further processing and analysis based on the measurement results of talent in the sports field. The measurement website page can display measurement results and identify type of talent that belongs to the child. Based on the results of measurement and data analysis, the accuracy of the tools for measuring body height were 98.7% and body weight were 99.5%, while the precision of the tools were 98.6% for body height and body weight were 97.4%.